Abrigos de morcegos hematófagos: identificação e mapeamento em áreas rurais dos Estados de São Paulo e Espírito Santo - Bernardo-Pedro, T.; Pereira, S. R. F. G.; Chicarino, C. N.; Vieira, L. F. P.; Azevedo, F. A. M.; Meireles, M. A. D.; Câmara, F. P. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2011)
n Brazil, there are 150 species of bats, all of them from suborder Microchiroptera. Three of them correspond to vampire bats: Desmodus rotundus, Diphylla ecaudata and Diaemus youngi. The common vampire bat D. rotundus has been the main reservoir of rabies virus in rural areas. Shelters of bats can be classified as natural or artificial. The study was conducted between 2008 and 2011. Twentyone shelters were mapped with a GPS unit. D. rotundus were captured in nine field trips, using mesh nets set up in front of shelters. Ten shelters were mapped in Campos dos Goytacazes; six were artificial and four were natural; they were located at S22°00’26,4’’–W041°40’00,3’’/S21o32’14,7’’–W041o20’31,3’’/S21o48’31,2’’– W041o38’20,7’’/S21o48’29,4’’–W041o38’22,0’’/S22o00’40,6’’–W041o39’98,0’’/ S21o57’53,2’’–W041o27’59,0’’/S21o58’18,3’’–W041o27’03,2’’/S21o47’09,6’’– W041o14’00,8’’/S21o46’02,6’’–W041o35’44,0’’/S21o47’54,2’’–W041o36’28,2’’. Six shelters were found in Cardoso Moreira; half of them were artificial, and the other half were natural; they were located at S21o32’07,5’’–W041o35’46,9’’/ S21o32’29,0’’–W041o36’31,8’’/S21o27’29,4’’–W041o34’36,2’’/S21o26’43,7’’– W041o33’43,1’’/S21o30’28,7’’–W041o27’20,5’’/S21o32’29,9’’–W041o36’31,8’’. Two shelters were mapped in Miracema; one was natural, and the other was artificial; their location was S21°23’39,3’’–W042°04’32,4’’/S21o19’29,1’’–W042o07’49,1’’. One shelter was found in Quissamã; it was artificial and located at S22°05’15,7’’– W041°41’20,2’’. Another shelter was found in Bom Jesus do Norte; it was artificial and located at S21°06’45,8’’–W041°40’55,6’’. The last shelter was mapped in Italva; it was natural and located at S21°27’06,4’’–W041°43’34,2’’. In a field trip to Campos dos Goytacazes (S22°00’26,4’’–W041°40’00,3’’), four male bats were captured. In Miracema (S21°23’39,3’’–W042°04’32,4’’), 28 males and 23 females were captured in three field trips. In Quissamã, 117 bats (59 males and 58 females) were captured in three field trips too. In a field trip to Bom Jesus do Norte, 26 males and 46 females were captured. In the last field trip, to Italva, one male and 13 females were captured. All mapped shelters were located in rural areas (distant from urban centers), and most of them were far from human habitations. Most shelters were artificial, showing the direct influence of humans on the spread of bats. All field trips were made during the day, except the one to Bom Jesus do Norte, made at night. In Italva, one vampire bat D. ecaudata was found.